Marine Isolates of Trimastix marina Form a Plesiomorphic Deep-branching Lineage within Preaxostyla, Separate from Other Known Trimastigids (Paratrimastix n. gen.) - Zhang, Qianqian; Táborský, Petr; Silberman, Jeffrey D; Pánek, Tomáš; Čepička, Ivan; Simpson, Alastair G B (Protist, 2015)
Trimastigids are free-living, anaerobic protists that are closely related to the symbiotic oxymonads, forming together the taxon Preaxostyla (Excavata: Metamonada). We isolated fourteen new strains morphologically corresponding to two species assigned to Trimastix (until now the only genus of trimastigids), Trimastix marina and Trimastix pyriformis. Unexpectedly, marine strains of Trimastix marina branch separately from freshwater strains of this morphospecies in SSU rRNA gene trees, and instead form the sister group of all other Preaxostyla. This position is confirmed by three-gene phylogenies. Ultrastructural examination of a marine isolate of Trimastix marina demonstrates a combination of trimastigid-like features (e.g. preaxostyle-like I fibre) and ancestral characters (e.g. absence of thickened flagellar vane margins), consistent with inclusion of marine T. marina within Preaxostyla, but also supporting its distinctiveness from 'freshwater T. marina' and its deep-branching position within Preaxostyla. Since these results indicate paraphyly of Trimastix as currently understood, we transfer the other better-studied trimastigids to Paratrimastix n. gen. and Paratrimastigidae n. fam. The freshwater form previously identified as T. marina is described as Paratrimastix eleionoma n. sp., and Trimastix pyriformis becomes Paratrimastix pyriformis n. comb. Because of its phylogenetic position, 'true' Trimastix is potentially important for understanding the evolution of mitochondrion-related organelles in metamonads.
Keywords: druhová specificita; Aquatic Organisms; vodní organismy; flagella; Phylogeny; RNA, Ribosomal, 18S; organely; Organelles; fylogeneze; Species Specificity; RNA ribozomální 18S; Flagella; Eukaryota